Climate finance - Climate leadership program - Chilambe, Pedro (2024)
Defining Climate Finance: Climate finance refers to local, national, and transnational funding to support mitigation and adaptation actions addressing climate change. • Funding Sources: Climate finance can come from public, private, and alternative sources, including governments, multilateral institutions, and private investors. • Key Objectives: The primary goals of climate finance are to invest in the reduction of greenhouse gas emissions and enhance resilience to the impacts of climate change as per commitments in NDCs.